An Enthusiastic Glance in to the Visible Responsive Photocatalysts for Energy Production and Pollutant Removal, with Special Emphasis on Titania - Padikkaparambil Silija; Zahira Yaakob; Viswanathan Suraja; Njarakkattuvalappil Narayanan Binitha; Zubair Shamsul Akmal (International Journal of Photoenergy)
As a consequence of the rapid growth of industry, major problems are created related to energy and environment. Sunlight being one of the most potential alternative source of energy, the development of efficient solar-energy storage systems is an important subject in the fields of science and technology. Here we have reviewed and summarized some of the recent reports on visible responsive photocatalysts. In this review, the influence of various metal oxide photocatalysts on energy production and pollutant removal are presented with special emphasis on titania based photocatalysts. The photoactivity of titania for various pollutant degradation, modified titania (TiO2) systems, their physical and chemical characteristics, and so forth, are described in detail at this juncture. Different methods used to enhance the visible light absorption of TiO2, like doping with metals and nonmetals, coupling with other metal oxides, and so forth, have been discussed. Various applications of photocatalysts including photocatalytic treatment of waste water, pesticide degradation and water splitting to produce hydrogen are summarized. The development of photocatalysts that function under visible light for the efficient utilization of sunlight is an area of current interest and thus the different methods of preparation for the visible active photocatalysts are also explored.